Multidimensional poverty in Nigeria: First order dominance approach - Olu Ajakaiye; Afeikhena T. Jerome; Olanrewaju Olaniyan; Kristi Mahrt; Olufunke A. Alaba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This study appraises non-monetary multidimensional poverty in Nigeria using the novel first order dominance approach developed by Arndt et al. (2012). It examines five dimensions of deprivation: education, water, sanitation, shelter, and energy-using comparable datasets, the Nigeria Demographic and Health Surveys of 1999, 2003, and 2008 for national, regional, and zonal analysis, and the Harmonized Nigeria Living Standard Survey of 2008/09 as well as the Nigeria Living Standard Survey of 2003/04 for state analysis. The results are quite robust and lend support to the general view that poverty in Nigeria has not kept pace with the rapid economic growth attained in the last decade. The country registered only fewer gains in non-income poverty. There was a marginal change of -0.21 in the percentage of the population experiencing acute deprivation between 1999 and 2008 and only one of the indicators (sanitation) recorded a substantial positive change. The spatial first order dominance comparisons indicate that regional inequalities remain profound with huge disparities in states as shown by the bootstrap. Ten of the worst-ranked states are located in the northern part of the country.
Keywords: I30; I31; I32; O12; 330; development; multidimensional poverty; ordinal dominance; welfare; well-being; Nigeria